REVIEW OF THE LITERATURE ON SEPSIS IN CALVES AND MEASURES TO PREVENT IT (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article describes sepsis that occurs in calves, that is, colibacteriosis, the causes of occurrence, diagnosis, the causes of the occurrence of this disease, the morphological and physiological changes that occur in calves, the indicators and complications ofdeath.